Intrapersonal Communication in the Process of Establishing the Self-Concept of Communications Students of the State Islamic University of North Sumatera - Dina Aulia; Indira Fatra Deni (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
The purpose of this article is to learn how communication science students at the State Islamic University of North Sumatra conduct intrapersonal communication in order to form a self-concept. Building one's self-concept must begin with intrapersonal communication, which is accompanied by psychological processes. The researchers want to look into the process and impact of intrapersonal communication among communication science students at the State Islamic University of North Sumatra on self-concept formation. This study is qualitative descriptive in nature, with data collected through interviews, observation, and documentation. According to the findings of this study, the majority of students who serve as resource persons in this study do not understand self-concept and do not engage in intrapersonal communication. Individuals with an immature self-concept as a result of poor intrapersonal communication have no interest in pursuing achievement, stifling the mental revolution. Meanwhile, students who successfully engage in intrapersonal communication develop a self-concept that allows them to achieve success.